Perlindungan Hukum bagi Pemegang Hak Guna Usaha Perkebunan yang Telah Berakhir terhadap Gugatan Perdata oleh Pemegang Hak Konsesi di Pengadilan: Studi Putusan Nomor 507/Pdt/2021/Pt Mdn - M Faqih Akbar; Ok Saidin; Aflah (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study aims to analyze the legal regulation of concession rights that have not been converted under Indonesian agrarian law, examine the forms of legal protection for holders of expired Cultivation Rights Title (Hak Guna Usaha/HGU), and analyze judicial considerations in Decision Number 507/Pdt/2021/PT MDN. This research employs normative legal research using statutory, historical, and case approaches. The findings indicate that concession rights originating from the colonial period must be converted into the national agrarian legal system under the Basic Agrarian Law of 1960. Unconverted concession rights no longer possess legal force as a basis for land control. Regarding land with expired HGU status, the state remains the authority holding control over the land, while former HGU holders continue to receive legal protection in the form of priority rights to reapply for land rights in accordance with applicable regulations. In Decision Number 507/Pdt/2021/PT MDN, the panel of judges emphasized that the expiration of HGU does not automatically return the land to parties claiming former concession rights, but instead the land remains under state control. The decision demonstrates the importance of legal certainty, legal protection, and consistency in the application of the national agrarian legal system in resolving land disputes in Indonesia.